Should we enhance animals? - Chan, S. (Journal of medical ethics, 2009)
Much bioethical discussion has been devoted to the subject of human enhancement through various technological means such as genetic modification. Although many of the same technologies could be, indeed in many cases already have been, applied to non-human animals, there has been very little consideration of the concept of “animal enhancement”, at least not in those specific terms. This paper addresses the notion of animal enhancement and the ethical issues surrounding it. A definition of animal enhancement is proposed that provides a framework within which to consider these issues; and it is argued that if human enhancement can be considered to be a moral obligation, so too can animal enhancement.